12x+2=13+x

Simple and best practice solution for 12x+2=13+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+2=13+x equation:



12x+2=13+x
We move all terms to the left:
12x+2-(13+x)=0
We add all the numbers together, and all the variables
12x-(x+13)+2=0
We get rid of parentheses
12x-x-13+2=0
We add all the numbers together, and all the variables
11x-11=0
We move all terms containing x to the left, all other terms to the right
11x=11
x=11/11
x=1

See similar equations:

| 9w^2+9w-54=11w+3 | | 2^3x+1×5^4x-2=110 | | 2^4x^-1=32 | | -18x+36=36-18x | | (y+4)−(y−1)=6y | | 625=5^-6x+^5 | | |5x-1|=|2x+5| | | 5^(3x-1)=49 | | 5^3x-1=49 | | 10.50x+3.75(82)=2071.50 | | 2x-1=9x+1 | | 19=6x/26 | | 28=6(x+3)-4x | | 6b+7=325 | | 0.06y=1.8 | | X/2+17=5x/8+4-x | | 2x+17=5x/8+4-x | | 7x+2-3x=14 | | X/2+5x/8=21-x | | 2x/5+3x/5=8+3 | | 8x-5-2x=25 | | 3n+9=5n-7 | | 7+4x(4-1)=19 | | 2x-4+9x=40 | | ─9r+4r─11+2=3r+7─8r+9 | | 32(40-4.5x)=16(4x-7)+60.8 | | 3(m-2)-2=4(m-4) | | 7(x-2)=-3(x+3)+33 | | 7(x—49)—5(x+49)=63–5(x—49) | | (2x)(5x)(11x)=360 | | q^2-q=42 | | 9t+81=0 |

Equations solver categories